Implications of dynamic factor models for VAR analysis - Stock, James H.; Watson, Mark W. 1952- (National Bureau of Economic Research, 2005)
"This paper considers VAR models incorporating many time series that interact through a few dynamic factors. Several econometric issues are addressed including estimation of the number of dynamic factors and tests for the factor restrictions imposed on the VAR. Structural VAR identification based on timing restrictions, long run restrictions, and restrictions on factor loadings are discussed and practical computational methods suggested. Empirical analysis using U.S. data suggest several (7) dynamic factors, rejection of the exact dynamic factor model but support for an approximate factor model, and sensible results for a SVAR that identifies money policy shocks using timing restrictions"--National Bureau of Economic Research web site.
Keywords: Ökonometrisches Modell; Econometric models